The Winchcombe fireball—That lucky survivor - McMullan, S.; Vida, D.; Devillepoix, Hadrien; Rowe, J.; Daly, L.; King, A. J.; Cupak, Martin; Howie, Robert; Sansom, Ellie; Shober, P.; Towner, Martin; Anderson, S.; et al. (Wiley-Blackwell, 2023)
On February 28, 2021, a fireball dropped ∼0.6 kg of recovered CM2 carbonaceous chondrite meteorites in South-West England near the town of Winchcombe. We reconstruct the fireball's atmospheric trajectory, light curve, fragmentation behavior, and pre-atmospheric orbit from optical records contributed by five networks. The progenitor meteoroid was three orders of magnitude less massive (∼13 kg) than any previously observed carbonaceous fall. The Winchcombe meteorite survived entry because it was exposed to a very low peak atmospheric dynamic pressure (∼0.6 MPa) due to a fortuitous combination of entry parameters, notably low velocity (13.9 km s−1). A near-catastrophic fragmentation at ∼0.07 MPa points to the body's fragility. Low entry speeds which cause low peak dynamic pressures are likely necessary conditions for a small carbonaceous meteoroid to survive atmospheric entry, strongly constraining the radiant direction to the general antapex direction. Orbital integrations show that the meteoroid was injected into the near-Earth region ∼0.08 Myr ago and it never had a perihelion distance smaller than ∼0.7 AU, while other CM2 meteorites with known orbits approached the Sun closer (∼0.5 AU) and were heated to at least 100 K higher temperatures.